Widespread non‐adherence to evidence‐based maternity care guidelines: a population‐based cluster randomised household survey. (22nd August 2014) - Nagpal, J; Sachdeva, A; Sengupta Dhar, R; Bhargava, VL; Bhartia, A
<x xml:space="preserve">Abstract</x> Objective To assess the quality of maternity care in an Indian metropolitan city. Study design Three‐stage cluster randomised cross‐sectional survey. Setting Sixty selected colonies of Delhi. Population One thousand eight hundred and one subjects (of 2286 eligible) were enrolled from 118 446 houses. Women who had delivered a live viable birth in the past 6 months were selected for the study. Methods In stage 1, 20 wards (of 150) were selected using a probability‐proportionate‐to‐size systematic method. In stage 2, one colony from each income stratum (high, middle and low) was selected from each ward by simple random sampling. In stage 3, a house‐to‐house survey was conducted to recruit 30 women for administering a peer‐reviewed and pilot‐trialled questionnaire. Main outcome measures Caesarean section rate, induction rate and episiotomy rate. Results National health targets such as iron supplementation advice (>96%), tetanus vaccination (>81%), and ≥3 antenatal visits (>90%) were largely achieved across health care facilities but not in home deliveries. Interventions were lower in public than private hospitals: caesarean section [23.7% (20.2–27.7) versus 53.8% (49.3–58.3)], induction [20.6% (17.5–24.25) versus 30.8% (26.8–33.2)] and episiotomy [57.8% (52.3–63.1) versus 79.4% (71.0–85.9)]. Private hospitals achieved better labour support rates [1.1% (0.5–2.2) versus 14.6% (8.5–24.1)] and pain relief [0.9% (0.4–2.0) versus 9.9 (6.5–14.8)]. Pubic hair shaving [16.2% (11.5–22.5) versus 36.4% (29.9–43.4)], enema [20.2% (15.5–26.0) versus 57.3% (49.5–64.8)], and IV fluids during labour [44.0% (36.2–52.2) versus 38.7% (29.3–49.1)] were widely prevalent in public and private hospitals. Conclusion Present practices fall short of evidence‐based guidelines, with relative overuse of interventions in private hospitals and deficiency of patient‐centred practices such as labour support in public hospitals.